Effect of Methionine Deficiency on the Growth Performance, Serum Amino Acids Concentrations, Gut Microbiota and Subsequent Laying Performance of Layer Chicks - Liu, Yafei; Wang, Dehua; Zhao, Lihong; Zhang, Jianyun; Huang, Shimeng; Ma, Qiugang (Frontiers in Veterinary Science, 2022)
This study was conducted to investigate the effect of methionine (Met) deficiency in the rearing period on the growth performance, amino acids metabolism, intestinal development and gut microbiome of egg-laying chicks and the continuous effects on the performance, egg quality, and serum amino acids metabolism of subsequent development process. A total of 360 one-day-old chicks were randomly divided into two groups and fed on a basal diet (NC group, Met 0.46%) and methionine deficiency diet (Met- group, Met 0.27%), each group included six replicates with 30 chicks per replicate. The trial lasted six weeks (0-6 weeks), the same basal diet was fed to carry out a continuous observation of the test chicks until the peak laying period. Results showed that methionine deficiency significantly decreased (P < 0.05) body weight (BW), average daily weight gain (ADG), average daily feed intake (ADFI) and tibia length (TL) compared to the NC group during the trial period (0-6 weeks), and dramatically increased (P < 0.05) feed conversion ratio (FCR) on the trial and observation period (7-24 weeks). Also, during the observation period, the BW and ADG were decreased (P < 0.05) in the Met- group. Moreover, Met- group decreased (P < 0.05) villi height and villi height/crypt depth ratio in jejunum at 6th weeks. In addition, the concentrations of serum main free amino acids (FAA) in the Met- group were significantly increased (P < 0.05) at 6th weeks, while were decreased at 16th weeks. Based on the α-diversity and PCoA analysis in β-diversity, no significant difference was observed in the cecal microbial composition between NC and Met- groups. However, the LEfSe analysis revealed that differential genera were enriched in the NC and Met- groups, respectively. The Haugh unit, shell thickness and egg production in the Met- group were significantly lower (P < 0.05) than that in the NC group. In conclusion, these results revealed that dietary supplementation of appropriate Met can significantly improve the growth performance, host amino acid metabolism, and intestinal development and continuously improved the laying performance and thus boost the health of growing hens.